The Emergence of Boundary Spanning Competence in Practice: Implications for Implementation and Use of Information Systems1 - Levina, Natalia; Vaast, Emmanuelle (MIS Quarterly, 2005)
This paper investigates how an organizational competence in boundary spanning emerges in practice by drawing on the concepts of boundary spanner and boundary object. Using data from two qualitative field studies, we argue that in order for boundary spanning to emerge a new joint field of practice must be produced. Our data illustrate that some agents partially transform their practices in local settings so as to accommodate the interests of their counterparts. While negotiating the new joint field, these agents become what we call boundary spanners-in-practice who produce and use objects which become locally useful and which acquire a common identity—hence, boundary objects-in-use. Moreover, we show how boundary spanners-in-practice use various organizational and professional resources including the influence that comes with being nominated to boundary spanners’ roles to create the new joint field. The conditions necessary for boundary spanners-in-practice to emerge are outlined and discussed, as are important implications for IS implementation and use.